Assessing the Factors Influencing Service Innovation Capabilities and Performance - Nor Asiah Omar; Syed Shah Alam; Azhar Ahmad; Muhamad Azrin Nazri (Information Management and Business Review, 2024)
Volume: 8 No: 4